Dirasah Taqabuliyyah Baina Istikhdami Litabai Al-Amtsilah At-Tashrifiyyah wa Qawa'idu Ash-Sharf Bi Uslubi Al-'Ashr Fi Talimi 'Ilmi Ash-Sharf. - Casrameko Casrameko (Jurnal Hikmatuna, 2016)
The exchange learned a big role in promoting Islamic sciences, because it has an important place in the Arabic language. Islamic science and often in Arabic but being stable in the administration told civilization and Islamic city since the corners of the country. As well as in the formation and development of civilization and culture of the nation because it is the knowledge and information that is was one of the development and evolution of the condition vessels. That shorof science learning to the students it is not an easy matter, because this learning requires knowledge of the properties of such shorof book Kitab al-amstilah at-tashrifiiyyah and book qowa'idu ash-shorfi usluubi bi al-Ashri, therefore we must comparing between them so that learning becomes easy after knowing the differences and similarities between both. Because each book has its advantages and disadvantages that can be complementary between them.